Spunti Italiano intermedio - Viale, Daniela (Open textbook library., 2019)
Welcome to Spunti: italiano intermedio – a unique program, authored by the Italian faculty of Muhlenberg College, that takes the place of a traditional language textbook. Spunti is a fully designed course that a college instructor of Italian can use and adapt.